Economic evaluation of alternative assisted reproduction techniques in management of infertility in Greece - Fragoulakis V; Kourlaba G; Tarlatzis B; Mastrominas M; Maniadakis N (Dove Medical Press, 2012)
Vassilis Fragoulakis,1 Georgia Kourlaba,1 Basil Tarlatzis,2 Minas Mastrominas,3 Nikolaos Maniadakis,11Department of Health Services Management, National School of Public Health, Athens; 2Unit of Human Reproduction, 1st Dept of OB/GYN, Medical School of Aristotle University of Thessaloniki, Thessaloniki; 3Embryogenesis Centre for Reproductive and Fertility Studies, Athens, GreeceBackground: The purpose of this study was to compare Gonal-F®, a recombinant follicle-stimulating hormone, with (Menopur®), a highly purified human menopausal gonadotrophin (hpHMG) in assisted reproduction in Greece.Methods: A decision tree in combination with a Markov model was used to assess the clinical and economical impact of comparators for up to three consecutive cycles. Transition probabilities were derived from the literature and validated by clinical experts. Cost components were derived from the electronic databases of selected private and public clinics. A probabilistic sensitivity analysis was performed to deal with uncertainty and to construct a cost-effectiveness acceptability curve.Results: There was a statistically significant difference in favor of the recombinant follicle-stimulating hormone arm compared with hpHMG, which was associated with 52 more births (95% uncertainty interval 26–78, P = 0.001) per 1000 patients. The cost per birth was estimated at €16,906 and €17,286 in the recombinant follicle-stimulating hormone and hpHMG arms, respectively. The cost per in vitro fertilization was estimated at €4365 in the recombinant follicle-stimulating hormone arm and €3815 in the hpHMG arm, indicating a difference of €550. The incremental cost per birth for recombinant follicle-stimulating hormone versus hpHMG was estimated at €14,540, while the incremental cost per life-year was estimated at €175.41.Conclusion: Recombinant follicle-stimulating hormone may represent a cost-effective choice compared with hpHMG when used for ovarian stimulation for a pharmacoeconomic point of view in the Greek public health care setting. However, it must be noted that in clinical practice both agents may be used together to increase the number of follicles, oocytes, embryos, and/or pregnancies in treated patients, an approach which has not been evaluated in Greece or reported in the literature due to obvious limitations.Keywords: cost-effectiveness, Gonal®, Menopur®, highly purified human menopausal gonatotrophin